Systematic review of basic oral care for the management of oral mucositis in cancer patients and clinical practice guidelines - Hong, Catherine H. L.; Gueiros, Luiz Alcino; Fulton, Janet S.; Cheng, Karis Kin Fong; Kandwal, Abhishek; Galiti, Dimitra; Fall-Dickson, Jane M.; Johansen, Jorgen; Ameringer, Suzanne; Kataoka, Tomoko; Weikel, Dianna; Eilers, June; et al. (Supportive care in cancer, 2019)
Purpose The aim of this study was to update the clinical practice guidelines for the use of basic oral care (BOC) interventions for the prevention and/or treatment of oral mucositis (OM). Methods A systematic review was conducted by the Mucositis Study Group of the Multinational Association of Supportive Care in Cancer/International Society for Oral Oncology (MASCC/ISOO). The body of evidence for each intervention in each cancer treatment setting was assigned an evidence level. The findings were added to the database used to develop the 2013 MASCC/ISOO clinical practice guidelines. Based on the evidence level, one of the following three guideline determinations was possible: Recommendation, Suggestion, No guideline possible. Results A total of 17 new papers across six interventions were examined and merged with a previous database. Based on the literature, the following guidelines were possible. The panel suggests that the implementation of multi-agent combination oral care protocols is beneficial for the prevention of OM during chemotherapy, head and neck (H&N) radiation therapy (RT), and hematopoietic stem cell transplantation (Level of Evidence III). The panel suggests that chlorhexidine not be used to prevent OM in patients undergoing H&N RT (Level of Evidence III). No guideline was possible for professional oral care, patient education, saline, and sodium bicarbonate, and expert opinion complemented these guidelines. Conclusions The evidence supports the use of multi-agent combination oral care protocols in the specific populations listed above. Additional well-designed research is needed on the other BOC interventions prior to guideline formulation.